Seasonal variability and fractionation of P-based nutrients in Sungai Setiu Basin, Terengganu, Malaysia - Hee, Yet Yin; Suhaimi Suratman,; Norhayati Mohd Tahir,; Jickells, Timothy (Penerbit Universiti Kebangsaan Malaysia, 2018)
A seasonal study of phosphorus (P)-based nutrients was carried out in Sungai Setiu basin which is located in the southern region of the South China Sea (Malaysia) from July 2010 until June 2011. Parameters measured were dissolved inorganic P (DIP), dissolved organic P (DOP) and total particulate P (TPP). In addition, DOP concentration was size fractionated into high molecular weight (HMW, 0.7 μm-100 kDa), middle MW (MMW, 100-30 kDa) and low MW (LMW, <30 kDa). The results show that the mean concentration of P-based nutrients ranged between 3.2-7.0 μg/L P for DIP, 5.6-12.1 μg/L P for DOP and 9.2-119.4 μg/L P for TPP. Higher mean concentrations of P were recorded at urban and agricultural areas. In addition, the distribution of P was affected by season as higher mean concentrations of P were observed during the north-east monsoon due to the surface runoff of nutrients during this heavy raining season. The fractionation study of DOP further revealed that HMW fraction was abundant in Sungai Setiu, making up approximately 60% of the total DOP. This high percentage of HMW DOP was recorded at stations in the vicinity of agriculture area and towns suggesting an important contribution from anthropogenic activities. The LMW DOP fraction was not significantly associated with chlorophyll-a, suggesting that the phytoplankton might not be the predominant contributor for LMW fraction in this river. We suggest that these organic nutrient inputs should be monitored as part of the management of the aquatic system.